TANGGUNG JAWAB DIREKSI TERHADAP TERJADINYA KREDIT MACET PADA PERBANKAN BERDASARKAN UNDANG-UNDANG NOMOR 40 TAHUN 2007 - Hasnati, Hasnati (Soumatera Law Review, 2019)
Banks are companies whose business activities are to raise funds, channel funds, and provide financial services. Of the three bank business activities, the distribution of funds is an activity that is a source of income spread over the bank. However, large profits are directly proportional to the high level of risk, namely the occurrence of bad credit. The problem that will be discussed in this study is how is the responsibility of bank directors regarding the occurrence of bad credit to companies based on Law Number 40 of 2007 concerning Limited Liability Companies? The method used in this study is normative legal research using the statutory approach. The results of this study are that based on Article 97 of Act No. 40 of 2007, the directors are fully responsible personally for the company's losses if the person concerned is guilty or negligent in carrying out his duties. That is, as the party that gives approval in lending, the bank directors must be fully responsible if the disbursed credit is a problem in the future and becomes bad credit which causes losses to the company.